Hierarchically structured porous materials: synthesis strategies and applications in energy storage. Issue 11 (24th August 2020) - Wu, Liang; Li, Yu; Fu, Zhengyi; Su, Bao-Lian
Abstract: To address the growing energy demands of sustainable development, it is crucial to develop new materials that can improve the efficiency of energy storage systems. Hierarchically structured porous materials have shown their great potential for energy storage applications owing to their large accessible space, high surface area, low density, excellent accommodation capability with volume and thermal variation, variable chemical compositions and well controlled and interconnected hierarchical porosity at different length scales. Porous hierarchy benefits electron and ion transport, and mass diffusion and exchange. The electrochemical behavior of hierarchically structured porous materials varies with different pore parameters. Understanding their relationship can lead to the defined and accurate design of highly efficient hierarchically structured porous materials to enhance further their energy storage performance. In this review, we take the characteristic parameters of the hierarchical pores as the survey object to summarize the recent progress on hierarchically structured porous materials for energy storage. This is the first of this kind exclusively to survey the performance of hierarchically structured porous materials from different porous characteristics. For those who are not familiar with hierarchically structured porous materials, a series of very significant synthesis strategies of hierarchically structured porous materials are firstly and briefly reviewed. This will be beneficial for those who want to quickly obtain useful reference information about the synthesis strategies of new hierarchically structured porous materials to improve their performance in energy storage. The effect of different organizational, structural and geometric parameters of porous hierarchy on their electrochemical behavior is then deeply discussed. We outline the existing problems and development challenges of hierarchically structured porous materials that need to be addressed in renewable energy applications. We hope that this review can stimulate strong intuition into the design and application of new hierarchically structured porous materials in energy storage and other fields.